Metabolic reprogramming due to hypoxia in pancreatic cancer: Implications for tumor formation, immunity, and more - Hao, Xiaodong; Ren, Yidan; Feng, Maoxiao; Wang, Qin; Wang, Yunshan (Biomedicine & pharmacotherapy, 2021)
Hypoxia is a common phenomenon in most malignant tumors, especially in pancreatic cancer (PC). Hypoxia is the result of unlimited tumor growth and plays an active role in promoting tumor survival, progression, and invasion. As the part of the hypoxia microenvironment in PC is gradually clarified, hypoxia is becoming a key determinant and an important therapeutic target of pancreatic cancer. To adapt to the severe hypoxia environment, cells have changed their metabolic phenotypes to maintain their survival and proliferation. Enhanced glycolysis is the most prominent feature of cancer cells' metabolic reprogramming in response to hypoxia. It provides the energy source for hypoxic cancer cells (although it provides less than oxidative phosphorylation) and produces metabolites that can be absorbed and utilized by normoxic cancer cells. In addition, the uptake of glutamine and fatty acids by hypoxic cancer cells is also increased, which is also conducive to tumor progression. Their metabolites are pooled in the hexosamine biosynthesis pathway (HBP). As a nutrition sensor, HBP, in turn, can coordinate glucose and glutamine metabolism. Its end product, UDP-GlcNAc, is the substrate of protein post-translational modification (PTM) involved in various signaling pathways supporting tumor progression. Adaptive metabolic changes of cancer cells promote their survival and affect tumor immune cells in the tumor microenvironment (TME), which contributes to tumor immunosuppressive microenvironment and induces tumor immunotherapy resistance. Here, we summarize the hypoxic microenvironment, its effect on metabolic reprogramming, and its contribution to immunotherapy resistance in pancreatic cancer. [Display omitted] •Pancreatic cancer is one of the most hypoxic cancers, with unique characteristics of fibrosis.•Hypoxia in pancreatic cancer induces metabolic reprogramming to promote tumor progression.•Hypoxia and hypoxia-induced metabolic rearrangement contribute to the immunosuppression in pancreatic cancer.